Experimental Investigation of the Mechanism of Foaming Agent Concentration Affecting Foam Stability. Issue 6 (25th July 2017) - Wang, Hetang; Li, Jia; Wang, Zhan; Wang, Deming; Zhan, Hanhui
Abstract: With the aim of determining the effect of foaming agent concentration (FAC) on foam stability, the half‐life of a selection of typical foaming agents was investigated at different concentrations using the FoamScan ® instrument. The surface tension of the bulk solution after foaming was tested using a surface tension meter. The FAC had a significant effect on foam stability at concentrations <1%, and a weak relationship at concentrations >1%. A significant turning point in the plot of foam stability versus FAC indicated maximum foam stability. The concentration at this point was defined as the optimal stability concentration, which is a guide in foam application. The micelles were thermodynamically unstable at low concentrations and degraded into surfactant solution, but were extremely stable at high surfactant concentrations that did not affect the stability of the foam. A turning point was also observed in the plot of surface tension versus FAC, beyond which the surface tension remained constant; the concentration at this point was defined as the no spherical micelle concentration. The influence of FAC on foam stability is explained in terms of mean bubble diameter ( d mb ) and bubble size distribution.